2021
DOI: 10.1017/jfm.2021.441
|View full text |Cite
|
Sign up to set email alerts
|

Elevated low-frequency free-stream vortical disturbances eliminate boundary-layer separation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
3
3
0
Order By: Relevance
“…At the highest levels of FST, the bubble could be suppressed due to the boundary layer transitioning before the strong adverse pressure-gradient region, which promotes separation. However, the results could also suggest the suppression of laminar separation due to streaks (at least for the current experimental configuration), which is supported by the recent numerical investigation by Xu & Wu (2021). They found that free-stream vortical disturbances of moderate level prevent the separation in a boundary-layer flow over a plate or concave wall, suggesting that the strong mean-flow distortion associated with the nonlinear streaks or Görtler vortices prevents separation.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…At the highest levels of FST, the bubble could be suppressed due to the boundary layer transitioning before the strong adverse pressure-gradient region, which promotes separation. However, the results could also suggest the suppression of laminar separation due to streaks (at least for the current experimental configuration), which is supported by the recent numerical investigation by Xu & Wu (2021). They found that free-stream vortical disturbances of moderate level prevent the separation in a boundary-layer flow over a plate or concave wall, suggesting that the strong mean-flow distortion associated with the nonlinear streaks or Görtler vortices prevents separation.…”
Section: Resultssupporting
confidence: 86%
“…A similar phenomenon could exist in our results, where critically energetic streaks generated by sufficiently elevated FST can suppress separation. In these cases, as in Xu & Wu (2021), we also observe streak amplitudes in the range of 10 %–15 % of the free-stream velocity, although, at lower amplitudes, an LSB is still present.
Figure 20.Chordwise evolution of the disturbance profiles scaled with for chordwise positions of ( a ) 0.250, ( b ) 0.300, ( c ) 0.325, ( d ) 0.350, ( e ) 0.375, ( f ) 0.400, ( g ) 0.425, ( h ) 0.450, ( i ) 0.475, ( j ) 0.500.
…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This could be due to the fact that increasing the level of FST with the roughness results in more energetic streaks (higher amplitudes), making the flow more resilient to separation. This was demonstrated numerically by Xu and Wu [56], who found that free-stream vortical disturbances of moderate level prevent separation in a boundary-layer flow over a plate or concave wall. It can be inferred that the strong mean-flow distortion associated with the streaks could prevent separation.…”
Section: The Combined Effects Of Roughness and Freestream Turbulencementioning
confidence: 81%